An integrated knowledge-based and optimization tool for the sustainable selection of wastewater treatment process concepts. (October 2016) - Castillo, A.; Cheali, P.; Gómez, V.; Comas, J.; Poch, M.; Sin, G.
Abstract: The increasing demand on wastewater treatment plants (WWTPs) has involved an interest in improving the alternative treatment selection process. In this study, an integrated framework including an intelligent knowledge-based system and superstructure-based optimization has been developed and applied to a real case study. Hence, a multi-criteria analysis together with mathematical models is applied to generate a ranked short-list of feasible treatments for three different scenarios. Finally, the uncertainty analysis performed allows for increasing the quality and robustness of the decisions considering variation in influent concentrations. For the case study application, the expert system identifies 5 potential process technologies and, using this input, the superstructure identifies membrane bioreactors as the optimal and robust solution under influent uncertainties and tighter effluent limits. A mutual benefit and synergy is achieved when both tools are integrated because expert knowledge and expertise are considered together with mathematical models to select the most appropriate treatment alternative. Highlights: Integration of knowledge-based systems and mathematical optimization is proposed. These tools were integrated to support selection wastewater treatment process concepts. An integrated knowledge-based and optimization tool enables optimal solutions. A shortlist of solutions assessed by the EDSS is optimized by the superstructure tool. Sensitivity analysis is applied to ensure robustness of the solutions.